On-Demand Degradable and Acid-Generating Polymers Using Phenacyl Ester Derivatives - Yeon, Hyemi; Kumar, Ameet; Song, Juhwan; Lee, Juho; Wang, Se Jun; Kim, Sang Yup; Cho, Jinhan; Cho, Daeheum; Kim, Tae Ann (American Chemical Society, 2024)
UV-triggered degradation is an efficient method for disposing of polymers that are no longer usable or needed. Although various photolabile molecules have been employed to design photodegradable polymers, the potential of phenacyl ester derivatives, which liberate acidic molecules upon UV exposure, remains largely unexplored in polymer materials. Our study presents the UV-triggered degradation of polymers by utilizing phenacyl ester derivatives as monomers and cross-linkers. Through computational simulations and experiments, we investigate the regioisomeric and substitution effects of these derivatives on UV degradation kinetics. Notably, when incorporating these derivatives as repeating units in linear polymers, we observe accelerated UV degradation kinetics compared with small molecules. Throughout the degradation process, the photogenerated acids effectively initiate the deprotection of acetal protecting groups and the depolymerization of acid-sensitive polymers. Furthermore, we develop UV-degradable thermosetting resins based on phenacyl ester cross-linkers, serving as matrix materials for carbon fiber-reinforced polymer (CFRP) composites. By utilization of the UV-triggered degradation of the resin, CFs can be efficiently retrieved and recycled, offering a sustainable solution for CF recycling. This study opens a new avenue for designing waste-free plastics that can trigger specific chemical reactions upon degradation, contributing to a more environmentally friendly disposal of polymer waste.